Optical properties of ablated graphene oxide in aqueous dispersions - Е.В. Селиверстова; Н.Х. Ибраев; Д.А. Темірбаева; Г.С. Омарова (Қарағанды университетінің хабаршысы. Физика сериясы)
The effect of laser radiation on the structural and optical properties of graphene oxide dispersed in water was studied. It was shown that under laser ablation a significant reduction in the size of graphene oxide sheets can be achieved. In this case, the resulting main parts of particles have a size of about 110–120 nm, and are similar to graphene quantum dots. The Raman spectra indicate the reduction of graphene oxide during laser radiation. The thickness of the formed particles practically was not changed, since the ID/IG ratio has close values. The prepared dispersions of graphene oxide exhibit wide luminescence bands in the region of 400–600 nm with a maximum of about 450 nm and a lifetime of 1.6 ns. It was shown that by laser ablation it is possible to achieve a significant increasing in the luminescent ability of graphene oxide in an aqueous solution. In this case, the luminescence intensity increased by almost 2 times, while the optical density of the solution was increased by only 5 % relative to the initial dispersion. The results can be used to create organic luminescent materials, in optical nanotechnology, as well as in photovoltaics, biophysics and bioimaging.